In-situ characterization method for conductivity-structure-catalytic activity of electrocatalyst
The in-situ electrical/electrochemical measurement circuit and Raman spectroscopy acquisition window are constructed through microelectrochemical cell technology and electron beam lithography process, which solves the problem of difficult to evaluate the conductivity and structural changes of the electrocatalyst, and realizes the conductivity of the catalyst and In-depth research on structural changes is suitable for the research and screening of different types of electrocatalysts.
Patent Information
- Application Number
- CN202411438211.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The prior art is difficult to accurately evaluate the conductivity and structural changes of catalysts in electrocatalytic reactions, resulting in the inability to effectively guide the design of high-efficiency catalysts, and commonly used measurement methods cannot reflect the conductive information in the actual reaction environment.
Using microelectrochemical cell technology, interfinger electrode arrays and catalyst nanoparticles assembly are produced through electron beam lithography technology, and in-situ electrical/electrochemical measurement circuits and Raman spectral acquisition windows are constructed to realize in-situ conductivity, electrocatalytic signals and Synchronous measurement of structural information, the relationship between the conductivity, structural changes and catalytic activity of the catalyst is studied.
It has achieved a comprehensive understanding of the conductivity mechanism and reaction mechanism of the catalyst in an actual electrocatalytic environment, made up for the shortcomings of traditional measurement methods, provided in-depth research on the performance and reaction mechanism of the catalyst, and is suitable for the research and screening of different types of electrocatalysts.
Smart Images

Figure CN119198875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical measurement and material characterization, and in particular to an in-situ characterization method for the conductivity-structure-catalytic activity of an electrocatalyst. Background Art
[0002] Electrocatalytic reactions involve: the transfer of charge between catalysts and catalysts and the transfer process at the catalyst / electrolyte interface. Among them, compared with the charge transfer process, the charge transfer process is often ignored, resulting in the inability to accurately evaluate the catalyst activity and guide the design of efficient catalysts. Most of the current transition metal oxides (such as Co3O4 for oxygen evolution reaction) and sulfide (such as MoS2 for hydrogen evolution reaction) catalysts are semiconductor materials rather than metal materials, and their intrinsic conductivity is often poor. This leads to the need for conductive additives (such as carbon nanomaterials) to enhance the conductivity of electrodes in practical applications, but the use of additives will bring many problems: such as covering active sites, hindering mass transfer, and increasing costs. Therefore, it is very important to clarify the relationship between catalyst conductivity, structural changes and catalytic activity.
[0003] At present, there are two main methods commonly used to study the conductivity of catalysts: (1) two-terminal electrode measurement, that is, using a multimeter to measure the conductivity on the catalyst without adding electrolyte. This method is a non-in-situ measurement and cannot reflect the in-situ conductivity information under the actual reaction conditions; (2) electrochemical impedance spectroscopy measurement, the conductivity information extracted is derived from the fitting of the equivalent circuit, and the error is large. Therefore, it is urgent to develop a new in-situ characterization technology that can take into account the electrical properties of the catalyst, the actual reaction environment, and the structural information. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an in-situ characterization method for the conductivity-structure-catalytic activity of an electrocatalyst that takes into account the electrical properties of the catalyst, the actual reaction environment and the structural information.
[0005] In order to solve the above problems, the in-situ characterization method of conductivity-structure-catalytic activity of an electrocatalyst described in the present invention comprises the following steps: ⑴ Preparation of micro electrochemical cell: (a) 32 electrodes are fabricated on a printed circuit board by electron beam lithography. (b) arbitrarily selecting two adjacent electrodes to fabricate an interdigitated electrode array pattern on a printed circuit board by electron beam lithography, and then forming an interdigitated electrode array by thermal evaporation; (c) A series of polymethyl methacrylate windows were fabricated in the interdigitated electrode array region by electron beam lithography, and then a catalyst nanoparticle solution with a concentration of 5 mg / ml was dropped onto the printed circuit board and allowed to dry naturally; (d) removing the polymethyl methacrylate film with acetone, so that the catalyst nanoparticles are precisely deposited on the windows of the interdigital electrode array region, forming a micro-nano device chip assembled by the particles; (e) Covering the micro-nano device chip with a 1-2 μm thick polymethyl methacrylate film as an inert protective layer, and then patterning the area of interest on the polymethyl methacrylate by electron beam lithography to expose the surface of the catalyst particles as the electrochemical reaction window and Raman spectrum collection window; the size of the window is 10-500 μm; (2) Open the reaction window, use a carbon rod as the counter electrode, an interdigitated electrode array as the working electrode, and silver / silver chloride or mercury / mercuric oxide as the reference electrode. The three-electrode system consisting of the counter electrode, the working electrode and the reference electrode forms an in-situ electrical / electrochemical measurement circuit to construct a micro-electrochemical environment; ⑶ In situ electrical and electrochemical measurements: Electrodes were drawn out on the printed circuit board with wires and connected to the source meter. An electrocatalytic voltage of 0.5-2.0 V was applied to the electrodes through the source meter. At the same time, a small bias voltage of 0-100 mV was applied to the micro-nano device between the interdigitated electrode arrays. The electrocatalytic signals and in-situ conductivity signals of the micro-nano device were collected respectively, realizing in-situ electrical and electrochemical synchronous measurements. ⑷ In situ Raman spectroscopy characterization: The in-situ Raman signal of the reaction window during the electrocatalytic reaction is collected by Raman spectroscopy to obtain the in-situ structural information of the catalyst; ⑸ Apply periodic catalytic voltage to test the dynamic response characteristics of the catalyst electrocatalytic signal and in-situ conductivity signal.
[0006] The printed circuit board in step (a) is a SiO2 / Si, quartz or sapphire substrate.
[0007] In the step (b), the interdigitated electrode array is a finger-shaped or comb-shaped electrode with a periodic pattern in the surface.
[0008] The catalyst nanoparticles in the catalyst nanoparticle solution in step (c) are any one of transition metal oxides, sulfides, nitrides, carbides or phosphides, and have a size ranging from nanometers to micrometers.
[0009] Compared with the prior art, the present invention has the following advantages: 1. The present invention prepares an interdigitated electrode array to form an in-situ electrical / electrochemical measurement circuit, and is also provided with an in-situ Raman spectrum to construct a three-dimensional electrochemical environment of conductivity-structure-catalytic activity. Therefore, the in-situ conductivity signal, electrocatalytic signal and Raman signal of the electrocatalyst can be collected simultaneously. In an actual electrocatalytic environment, the intrinsic conductivity of the particle catalyst and the interconnected conductive mechanism between particles can be studied while monitoring the conductivity, reaction current and dynamic structural evolution of the catalyst, thereby fully understanding the relationship between the conductive mechanism and reaction mechanism of the catalyst, making up for the shortcomings of traditional two-terminal electrode measurement and electrochemical impedance spectroscopy measurement.
[0010] 2. In the present invention, the electrocatalytic voltage is dynamically applied through a voltage amplifier, so that the time response characteristics of the catalyst performance can be studied, providing important information for understanding the interface transmission between particles.
[0011] 3. The present invention prepares micro-nano devices through electron beam lithography, thus obtaining a miniaturized and integrated measurement platform.
[0012] 4. After adopting the method of the present invention, the sample consumption is small and the test is convenient. It can be widely used to study the conduction mechanism and reaction mechanism of different types of electrocatalysts (metal oxides, sulfides, phosphides, etc.), and at the same time provides a new idea for screening catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0014] Figure 1 It is a schematic diagram of the present invention.
[0015] Figure 2 A diagram showing the manufacturing process of Co3O4 (left) and MoS2 (right) particle devices in the micro-electrochemical cell of the present invention.
[0016] Figure 3 An image of the microelectrochemical cell of the present invention shows a microelectrochemical cell (left) and a device at the center of the cell (right), in which individual Co3O4 or MoS2 particles are dispersed on an array of interdigitated electrodes to form channels between particles for measurement.
[0017] Figure 4 Polarization curves and in-situ conductivity curves of the Co3O4 (a) and MoS2 (b) catalysts of the present invention at different electrocatalytic voltages, and in-situ Raman spectra of the Co3O4 (c) and MoS2 (d) catalysts at different electrocatalytic voltages. DETAILED DESCRIPTION
[0018] like Figure 1As shown, an in-situ characterization method for the conductivity-structure-catalytic activity of an electrocatalyst comprises the following steps: ⑴Prepare micro-electrochemical cell, such as Figure 2 As shown: (a) Thirty-two electrodes (i.e., gold electrodes) are fabricated on a printed circuit board by electron beam lithography; the printed circuit board refers to a SiO2 / Si, quartz, or sapphire substrate.
[0019] (b) Two adjacent electrodes are arbitrarily selected to make an interdigitated electrode array pattern on a printed circuit board by electron beam lithography, and then an interdigitated electrode array is formed by thermal evaporation.
[0020] (c) A series of polymethyl methacrylate windows were fabricated in the interdigitated electrode array area by electron beam lithography, and then a catalyst nanoparticle solution with a concentration of 5 mg / ml was dropped onto the printed circuit board and allowed to dry naturally.
[0021] The catalyst nanoparticles in the catalyst nanoparticle solution refer to any one of transition metal oxides, sulfides, nitrides, carbides or phosphides, and their sizes are in the order of nanometers to micrometers. Other substances having catalytic effects on electrocatalytic reactions may also be used.
[0022] (d) removing the polymethyl methacrylate film with acetone, so that the catalyst nanoparticles are precisely deposited on the windows of the interdigital electrode array region, forming a micro-nano device chip assembled by the particles; (e) The micro-nano device chip is covered with a 1-2 μm thick polymethyl methacrylate film as an inert protective layer, and then the area of interest is patterned on the polymethyl methacrylate by electron beam lithography to expose the surface of the catalyst particles as the electrochemical reaction window and Raman spectrum collection window; the size of the window is 10-500 μm.
[0023] ⑵Open the reaction window, use a carbon rod as the counter electrode, an interdigitated electrode array as the working electrode, and silver / silver chloride or mercury / mercury oxide as the reference electrode. The three-electrode system consisting of the counter electrode, the working electrode and the reference electrode forms an in-situ electrical / electrochemical measurement circuit to construct a micro-electrochemical environment.
[0024] ⑶ In situ electrical and electrochemical measurements: Electrodes are drawn out on a printed circuit board with wires and connected to a source meter. An electrocatalytic voltage of 0.5 to 2.0 V is applied to the electrodes through the source meter, and the measurement accuracy can reach 1 pA. At the same time, a small bias voltage of 0 to 100 mV is applied to the micro-nano device between the interdigitated electrode arrays to collect the electrocatalytic signals and in-situ conductivity signals of the micro-nano device, respectively, to achieve in-situ electrical and electrochemical synchronous measurement.
[0025] Electrocatalytic voltage refers to the voltage at which electrocatalytic reaction occurs. Small bias voltage is a voltage much smaller than the electrocatalytic voltage applied to the interdigital electrodes, usually 0, 2, 5, 10, 20, 50 mV, etc.
[0026] ⑷ In situ Raman spectroscopy characterization: The in-situ Raman signal of the reaction window during the electrocatalytic reaction is collected by Raman spectroscopy to obtain the in-situ structural information of the catalyst.
[0027] ⑸ Apply periodic catalytic voltage to test the dynamic response characteristics of the catalyst electrocatalytic signal and in-situ conductivity signal.
[0028] In order to obtain a relatively strong Raman signal, the present invention can place the micro-nano device in a polydimethylsiloxane mold, and use calcium fluoride as a transparent cover to better focus the Raman laser.
[0029] The present invention uses a voltage amplifier to perform current setting, and can improve the accuracy of time response to about 20 milliseconds.
[0030] The present invention can perform time response measurement on electrocatalytic signals and in-situ conductivity signals by applying a periodic voltage with a controllable duty cycle on the counter electrode, thereby obtaining instantaneous information on charge transfer and reaction activity at the beginning and end of the reaction.
[0031] By using the method of the present invention, the following can be collected: (i) in-situ conductivity signals; (ii) electrocatalytic signals, which reveal the charge transfer behavior between adjacent catalysts and the reaction activity during the reaction; (iii) in-situ Raman signals, which show the dynamic structural changes of the catalyst during the electrocatalytic process; and (iv) the time response of in-situ conductivity and electrocatalytic activity.
[0032] The electrolyte can be any conventional electrolyte in the art, as long as it does not react with the catalyst.
[0033] In the following cases, for the oxygen evolution reaction over Co3O4 catalyst, the electrocatalytic voltage ranges from 0.93 V to 1.63 V (compared to the reversible hydrogen electrode); for the hydrogen evolution reaction over MoS2 catalyst, the electrocatalytic voltage ranges from 0.29 V to -0.431 V (compared to the reversible hydrogen electrode).
[0034] Example 1 In situ electrical / electrochemical / Raman characterization of Co3O4 catalyst (1) Preparation of Co3O4 catalyst particles: Using a solvothermal method, 0.08 g of cobalt nitrate was dissolved in a mixture of 30 ml of isopropanol and 6 ml of glycerol. The mixture was reacted at 180°C for 6 hours. The resulting product was calcined at 350°C for 2 hours to obtain Co3O4 nanoparticles with an average diameter of 300-400 nm.
[0035] (2) Assembly of Co3O4 catalyst micro-nano devices: refer to Figure 2 According to the process shown in the figure, an interdigital electrode array (Ti / Au 5 / 70 nm) was fabricated on a printed circuit board, and then a polymethyl methacrylate window was opened by electron beam lithography, and a Co3O4 nanoparticle solution with a concentration of 5 mg / ml was dripped in. Finally, a polymethyl methacrylate film was covered again, and a reaction window was opened by electron beam lithography to obtain a micro-nano device with Co3O4 particles deposited. The particle-covered area was used as the reaction window, as shown in FIG. Figure 3 shown.
[0036] (3) In-situ electrical / electrochemical / Raman testing: The Co3O4 device was placed in a 1.0 M KOH electrolyte on a micro-electrochemical cell. An electrocatalytic voltage of 0.93 to 1.63 V (compared to the reversible hydrogen electrode) was applied to the counter electrode. At the same time, a small bias voltage of 0 to 50 mV was applied to the interdigitated electrode array. The polarization curve and conductivity signal of the catalyst were collected, and the in-situ Raman spectral signals at different voltages were simultaneously collected.
[0037] (4) Data analysis: Figure 4 a It can be seen that the Co3O4 catalyst exhibits significant conductive switching characteristics at the oxygen evolution reaction potential, and the in-situ conductive current increases by about 4 orders of magnitude compared to that before the reaction. From the Raman data, it can be seen (such as Figure 4 (c) During the oxygen evolution reaction, Co3O4 becomes amorphous but still maintains a highly conductive state, indicating that this conductive behavior originates from the self-gating effect on the catalyst surface rather than bulk conductivity.
[0038] Example 2 In situ electrical / electrochemical / Raman characterization of MoS2 catalyst (1) Preparation of MoS2 catalyst particles: Commercial MoS2 particles were filtered and classified to obtain MoS2 particles with a size of 0.5-2 μm.
[0039] (2) Assembling MoS2 catalyst micro-nano devices: The preparation process is similar to that of Co3O4 devices. An interdigitated electrode array (Ti / Au / Ti 5 / 50 / 20 nm) is made on a printed circuit board. Then, the polymethyl methacrylate window is opened by electron beam lithography, and a MoS2 nanoparticle solution with a concentration of 5 mg / ml is dripped in. Finally, the polymethyl methacrylate film is covered again, and the reaction window is opened by electron beam lithography to obtain a micro-nano device with MoS2 particles deposited. The particle-covered area serves as the reaction window, such as Figure 3 shown.
[0040] (3) In situ electrical / electrochemical / Raman testing: The MoS2 device was placed in a 0.5 M H2SO4 electrolyte, an electrocatalytic voltage of 0.29 to -0.431 V (compared to the reversible hydrogen electrode) and a small bias of 0-50 mV were applied, and the electrocatalytic current, in situ conductivity current signal and Raman spectral signal were collected.
[0041] (4) Data analysis: MoS2 catalyst also exhibits obvious conductive switching characteristics at the hydrogen evolution reaction potential, such as Figure 4 As shown in b, the in-situ conductivity current increases by about 3 orders of magnitude. However, its Raman spectrum does not change significantly during the hydrogen evolution reaction, such as Figure 4 As shown in (d), it shows that the improvement of the conductivity of MoS2 catalyst is mainly due to the surface self-gating effect rather than the change of bulk structure.
Claims
1. An in-situ characterization method for the conductivity-structure-catalytic activity of an electrocatalyst, comprising the following steps: ⑴ Preparation of micro electrochemical cell: (a) 32 electrodes are fabricated on a printed circuit board by electron beam lithography. (b) arbitrarily selecting two adjacent electrodes to fabricate an interdigitated electrode array pattern on a printed circuit board by electron beam lithography, and then forming an interdigitated electrode array by thermal evaporation; (c) A series of polymethyl methacrylate windows were fabricated in the interdigitated electrode array region by electron beam lithography, and then a 5 mg / ml catalyst nanoparticle solution was dropped onto the printed circuit board and allowed to dry naturally. (d) removing the polymethyl methacrylate film with acetone, so that the catalyst nanoparticles are precisely deposited on the windows of the interdigital electrode array region, forming a micro-nano device chip assembled by the particles; (e) Covering the micro-nano device chip with a 1-2 μm thick polymethyl methacrylate film as an inert protective layer, and then patterning the area of interest on the polymethyl methacrylate by electron beam lithography to expose the surface of the catalyst particles as the electrochemical reaction window and Raman spectrum collection window; the size of the window is 10-500 μm; (2) Open the reaction window, use a carbon rod as the counter electrode, an interdigitated electrode array as the working electrode, and silver / silver chloride or mercury / mercuric oxide as the reference electrode. The three-electrode system consisting of the counter electrode, the working electrode and the reference electrode forms an in-situ electrical / electrochemical measurement circuit to construct a micro-electrochemical environment; ⑶ In situ electrical and electrochemical measurements: Electrodes were drawn out on the printed circuit board with wires and connected to the source meter. An electrocatalytic voltage of 0.5-2.0 V was applied to the electrodes through the source meter. At the same time, a small bias voltage of 0-100 mV was applied to the micro-nano device between the interdigitated electrode arrays. The electrocatalytic signals and in-situ conductivity signals of the micro-nano device were collected respectively, realizing in-situ electrical and electrochemical synchronous measurements. ⑷ In situ Raman spectroscopy characterization: The in-situ Raman signal of the reaction window during the electrocatalytic reaction is collected by Raman spectroscopy to obtain the in-situ structural information of the catalyst; ⑸ Apply periodic catalytic voltage to test the dynamic response characteristics of the catalyst electrocatalytic signal and in-situ conductivity signal.
2. The in-situ characterization method for conductivity-structure-catalytic activity of an electrocatalyst according to claim 1, characterized in that: The printed circuit board in step (a) is a SiO2 / Si, quartz or sapphire substrate.
3. The in-situ characterization method for conductivity-structure-catalytic activity of an electrocatalyst according to claim 1, characterized in that: In the step (b), the interdigitated electrode array is a finger-shaped or comb-shaped electrode with a periodic pattern in the surface.
4. The in-situ characterization method for conductivity-structure-catalytic activity of an electrocatalyst according to claim 1, characterized in that: The catalyst nanoparticles in the catalyst nanoparticle solution in step (c) are any one of transition metal oxides, sulfides, nitrides, carbides or phosphides, and have a size ranging from nanometers to micrometers.
Citation Information
Patent Citations
In-situ electrochemical-surface enhanced raman spectroscopy (EC-SERS) detection system and detection method thereof
CN104215624A
Production method of field effect electrocatalytic hydrogen production device based on MoS2 nanosheet
CN106521549A
Method for carrying out electrochemical test by using micro device
CN115931988A
